Mechanism and Prevention of Ototoxicity Induced by Aminoglycosides - Fu, Xiaolong; Wan, Peifeng; Li, Peipei; Wang, Jinpeng; Guo, Siwei; Zhang, Yuan; An, Yachun; Ye, Chao; Liu, Ziyi; Gao, Jiangang; Yang, Jianming; Fan, Jiangang; et al. (Frontiers in Cellular Neuroscience, 2021)
Aminoglycosides, a class of clinically important drugs, are widely used worldwide against gram-negative bacterial infections. However, there is growing evidence that aminoglycosides can cause hearing loss or balance problems. In this article, we mainly introduce the main mechanism of ototoxicity induced by aminoglycosides. Genetic analysis showed that the susceptibility of aminoglycosides was attributable to mutations in mtDNA, especially A1555G and C1494T mutations in 12S rRNA. In addition, the overexpression of NMDA receptors and the formation of free radicals also play an important role. Understanding the mechanism of ototoxicity induced by aminoglycosides is helpful to develop new therapeutic methods to protect hearing. In this article, the prevention methods of ototoxicity induced by aminoglycosides were introduced from the upstream and downstream aspects.